Artes mágicas na Bahia quinhentista : o caso de Maria Gonçalves Cajada - Araujo, Gilmara Cruz de (2016)
The main objective of this research is to analyze the magical practices performed by Maria GonçalvesCajada, known as "Arde-lhe o rabo", in Bahia, in the 16th century. For this proposal, we analyze some cases, confessions and denunciations of the first visitation of the Holy Office in Bahia (1591-1593). These inquisitorial documents are in the custody of the National Archives of Torre do Tombo (ANTT – Arquivo Nacional da Torre do Tombo, in Portuguese), in Lisbon, Portugal, but have been digitized and are available on the institution's website. From a case study, we analyzed the magical practices, reasons for demands, the elements that make these practices and the female religious universe. Starting mainly from studies that revolve around the Micro History and Evidential Paradigm as the Italian historian Carlo Ginzburg suggested, the methodology adopted is not for a globalizing idea, nor build definitive conclusions and much less homogeneous, but possibilities that the evidence, clues and traces indicated in such way.